"A novel mixed-mode OTA-C filter" - Abuelma’atti, M.T. (2003)
A novel mixed-mode biquad circuit is presented. The circuit uses six single-output- and one dual-output-operational transconductance amplifiers, two grounded capacitors; and can realize lowpass, highpass, bandpass, notch, lowpass-notch, highpass-notch and allpass responses from the same topology. The circuit can be driven by voltage or current and its output can be voltage or current. The parameters ? o and ? o / Q o enjoy independent electronic tunability. Simulation results are included.